2021
DOI: 10.21203/rs.3.rs-885648/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“COVID Affected Us All:” The Birth and Postnatal Health Experiences of Resettled Syrian Refugee Women During COVID-19 in Canada

Abstract: Background: Prior to COVID-19, postnatal resettled refugee women in Canada reported barriers to healthcare and low levels of social support, contributing to maternal health morbidities. The COVID-19 pandemic appears to be further exacerbating health inequities for marginalized populations—yet the experiences of resettled refugee women are not fully known. Aim: To understand Syrian refugee women’s experiences accessing postnatal healthcare services and supports during the COVID-19 pandemic. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A study from central Ethiopia supports these findings, revealing that women who did not fear COVID-19 infection were about three times more likely to utilize maternal health services during the pandemic in comparison to those who feared infection [ 36 ]. Several studies reported that the fear of becoming infected in hospitals was the reason for lower PNC use [ 9 , 10 , 11 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from central Ethiopia supports these findings, revealing that women who did not fear COVID-19 infection were about three times more likely to utilize maternal health services during the pandemic in comparison to those who feared infection [ 36 ]. Several studies reported that the fear of becoming infected in hospitals was the reason for lower PNC use [ 9 , 10 , 11 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this essential service is neglected, with more emphasis placed on antenatal and intrapartum care [ 6 ]. Moreover, the coronavirus disease (COVID-19), emerging from the Hubei Province in the People’s Republic of China in December 2019 and subsequently spreading throughout the world, has resulted in alterations to healthcare structures and processes, such as reduced maternity service provision, including PNC [ 7 , 8 , 9 , 10 , 11 , 12 ]. However, to our knowledge, only a few studies have examined the PNC uptake using a quantitative approach during the pandemic in Ethiopia [ 13 ], Bangladesh [ 14 ], and the UK [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation